2005
DOI: 10.1111/j.1365-2044.2004.04119.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of direct laryngoscopy and jaw thrust to aid fibreoptic intubation*

Abstract: SummaryWe compared two manoeuvres, jaw thrust and laryngoscopy, to open the airway during fibreoptic intubation in 50 patients after induction of anaesthesia in a crossover study. Patients were randomly allocated to receive either jaw thrust or conventional Macintosh laryngoscopy first. Airway clearance was assessed at both the soft palate and the epiglottis. Direct laryngoscopy provided significantly better airway clearance at the level of the soft palate than jaw thrust (44 (88%) vs 31 (62%), respectively; p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 22 publications
2
54
0
Order By: Relevance
“…However, our endpoint allowed a crossover design and so increased the overall power of our study, and we were particularly interested in the degree to which the two techniques would result in airway clearance, which we felt was best assessed by the ease with which the vocal cords could be viewed. Dugra et al devised a subjective scoring system to describe the degree of obstruction of view during fibrescopy [8] and this scale was also used by Stacey et al [9]. We chose not to use a subjective scale, as we felt that poor views should be reflected in a longer time (or failure) to view the vocal , pages 1048-1052 .…”
Section: Discussionmentioning
confidence: 99%
“…However, our endpoint allowed a crossover design and so increased the overall power of our study, and we were particularly interested in the degree to which the two techniques would result in airway clearance, which we felt was best assessed by the ease with which the vocal cords could be viewed. Dugra et al devised a subjective scoring system to describe the degree of obstruction of view during fibrescopy [8] and this scale was also used by Stacey et al [9]. We chose not to use a subjective scale, as we felt that poor views should be reflected in a longer time (or failure) to view the vocal , pages 1048-1052 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies [4,12] suggest that the jaw-thrust manoeuvre provides a clear view at the epiglottis but not at the soft palate level. When lingual traction was combined with jaw thrust, the airway was cleared at both the soft palate and epiglottic levels in all patients [4].…”
Section: Discussionmentioning
confidence: 99%
“…However, lingual traction can injure the tongue tissue. Moreover, Stacey et al [12] compared two manoeuvres, jaw thrust and direct laryngoscopy, to open the airway during fibreoptic intubation, and showed that direct laryngoscopy provided significantly better airway clearance at the level of the soft palate than did jaw thrust, although airway clearance was equally good at the epiglottis level. However, laryngoscopic assistance can increase cardiovascular responses [13], and is difficult to use in patients with cervical spine abnormalities or weak teeth.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, BIF requires a short preparation time and it can be used quickly in an emergency situation [11]. Although intubation can be done using an FOB or BIF without any assisting device, even in difficult airways, there have been several studies that the difficult intubation can be facilitated by direct laryngoscopy (DL) [11-13]. Accordingly, it might be preferable to perform intubation using FOB or BIF assisted by direct laryngoscopy in difficult intubation patients.…”
Section: Introductionmentioning
confidence: 99%